Fibrotic microtissue array to predict anti-fibrosis drug efficacy - Mohammadnabi Asmani (Nature Portfolio, 2018)
A bottleneck in developing new anti-fibrosis therapies is the absence of suitable in vitro models that recapitulate key features of fibrogenesis. Here the authors develop a tissue-on-a-chip model of lung fibrosis and test the therapeutic efficacy of two recent FDA-approved drugs.